Adsorptive Removal of Cr (VI) from Aqueous Solution onto Charred Sugar Cane Bagasse - Bhatt, Puspa Raj; Aryal, Ram Lochan; Poudel, Bhoj Raj; Bhattarai, Sitaram; Gautam, Surendra Kumar (Journal of Nepal Chemical Society, 2018)
Available with full text.